Alienação em Karl Marx e o cinema como formação prático-crítica - Praciano, Emerson Ellano Dutra (2022)
The present research presents the formation and trajectory of the pedagogical project developed for more than ten years in public schools in the State of Ceará, called Cine Marvin: philosophical thinking in short films. By relating Philosophy, Alienation, Marxism and Cinema, we argue that the audiovisual activities produced by high school students from EEM Professora Eudes Veras and EEMTI Albaniza Rocha Sarasate with philosophical themes can be considered products of a philosophizing that goes beyond classroom debates . Pedagogical praxis takes place on the basis of short films so that they can be used as an educational reference in Philosophy classes, in addition to awakening skills so that students can learn cinematographic techniques and problematize philosophical content from reflection when producing and watching videos. . Considering, therefore, as a starting point, the discussion, the articulation between the educational practice and the learning process inserted in the construction of an audiovisual production through the work of teaching and active study with young people from the periphery of Fortaleza and Maracanaú can contribute to more critical students and less alien to the other and to the world.